Elucidation of Relevant Neuroinflammation Mechanisms Using Gene Expression Profiling in Patients with Amyotrophic Lateral Sclerosis. - Yu Hui Won; Min-Young Lee; Young-Chul Choi; Yoon Ha; Hyongbum Kim; Do-Young Kim; Myung-Sun Kim; Ji Hea Yu; Jung Hwa Seo; MinGi Kim; Sung-Rae Cho; Seong-Woong Kang (PLoS ONE, 2016)
Amyotrophic lateral sclerosis (ALS) is a progressive neurodegenerative disorder characterized by damage of motor neurons. Recent reports indicate that inflammatory responses occurring within the central nervous system contribute to the pathogenesis of ALS. We aimed to investigate disease-specific gene expression associated with neuroinflammation by conducting transcriptome analysis on fibroblasts from three patients with sporadic ALS and three normal controls. Several pathways were found to be upregulated in patients with ALS, among which the toll-like receptor (TLR) and NOD-like receptor (NLR) signaling pathways are related to the immune response. Genes-toll-interacting protein (TOLLIP), mitogen-activated protein kinase 9 (MAPK9), interleukin-1β (IL-1β), interleukin-8 (IL-8), and chemokine (C-X-C motif) ligand 1 (CXCL1)-related to these two pathways were validated using western blotting. This study validated the genes that are associated with TLR and NLR signaling pathways from different types of patient-derived cells. Not only fibroblasts but also induced pluripotent stem cells (iPSCs) and neural rosettes from the same origins showed similar expression patterns. Furthermore, expression of TOLLIP, a regulator of TLR signaling pathway, decreased with cellular aging as judged by changes in its expression through multiple passages. TOLLIP expression was downregulated in ALS cells under conditions of inflammation induced by lipopolysaccharide. Our data suggest that the TLR and NLR signaling pathways are involved in pathological innate immunity and neuroinflammation associated with ALS and that TOLLIP, MAPK9, IL-1β, IL-8, and CXCL1 play a role in ALS-specific immune responses. Moreover, changes of TOLLIP expression might be associated with progression of ALS.